#TITLE_ALTERNATIVE# - MIYONDRI (NIM : 12207036), DODI
There were so many different methods proposed to increase hydrocarbon production recovery. However, the methods are not always an optimum solution. This mainly because of the configuration used in the production of hydrocarbons is not the suitable. A common method used to determine the configuration is trial and error. This method is guided by qualitative analysis based on solely engineering judgment. The method tries to find the most optimum configuration of some scenarios although there is no exact optimum solution in such scenario. Specific optimization technique is required to find the near optimum production strategy. A stochastic optimization technique is believed to have advantages in solving optimization problem which their mathematic model is hardly to be developed. This final project aims to introduce stochastic based optimization methods and make comparisons among software that based on stochastic methods. They are OpTool and CMOST. The control parameters used were well placement, injection rate. The objective functions are cumulative oil production and net present value. The tools were used to maximize the objective functions. Simulation result shows OpTool software is good on cumulative oil production and net present value optimization.